Kinky spine or Scoliosis in Nilagiri lamb - KUMAR, R ANIL; SRINIVASAN, P; IYUE, M (The Indian Journal of Animal Reproduction, 2023)
A case of Scoliosis, a congenital malformation of axial skeleton in Nilagiri lambs has been reported.